Stories screen narrative in the digital era - Christie, Ian 1945-; Oever, Annie van den 1957- (Amsterdam University Press, 2018)
Stories are central drivers of media today - not only do they propel plot-driven entertainment media, such as television, cinema, theatre, but also social media. Telling and having a story is widely deemed essential, both in the large and widely visible world of commerce and in the everyday social lives of individuals. Does this dynamic represent an intensification of what has always been part of culture and civilization, or has it reached a new universality?
Erscheint auch als Open Access bei De Gruyter
Keywords: Erzähltechnik; Fernsehserie; Film; Storytelling in mass media; Aufsatzsammlung